Simultaneous Occurrence of HER2 Mutations in EGFR Mutant NSCLC: Case Reports - Blerina Resuli, MD; Diego Kauffmann-Guerrero, MD; Jürgen Behr, MD; Amanda Tufman, MD (JTO Clinical and Research Reports)
HER2 mutation and amplification have been identified as distinct molecular targets in lung cancer with different therapeutic and prognostic values. The coexistence of HER2 and EGFR mutations is extremely rare, and therefore, no data exist on the best treatment in these cases.